Donor Coordination and Harmonization in Bangladesh : A Joint Evaluation Paper - Thornton, Paul; Kolkma, Walter; Fostvedt, Nils (Washington, DC: World Bank, 2017)
In recent years, issues of aid effectiveness have come centre stage, motivated amongst other factors by the increased emphasis on impact evidenced in particular by the UN Millennium Development Goals (MDGs). Improved aid alignment and harmonization (A&H) is seen as vital for enhanced aid effectiveness, as reflected most prominently in the 2005 Paris Declaration. In this context, this Joint Evaluation Paper (JEP) addresses key aspects of donor coordination and harmonization in Bangladesh. The subject of the JEP is the Joint Strategic Framework (JSF) of the four largest aid donors in Bangladesh the World Bank (WB), Asian Development Bank (ADB), Department for International Development (DFID), and Japan. At the time it was started around 2005, the JSF was considered a major step forward in aid A&H, and as such merits serious joint evaluation.